Non-traumatic Acute Epidural Hematoma in Multiple Sclerosis Treated With Fingolimod - Fukai, Ryoko; Takahashi, Keita; Abe, Hiroyuki; Higashiyama, Yuichi; Doi, Hiroshi; Takeuchi, Hideyuki; Tanaka, Fumiaki (Frontiers in Neurology, 2019)
Fingolimod acts as a functional antagonist of the sphingosine-1-phosphate receptor and is widely used for relapsing-remitting multiple sclerosis (MS). Here we report the first case of non-traumatic acute epidural hematoma in a relapsing-remitting MS patient treated with fingolimod. Fingolimod might increase the risk of hemorrhage by enhancing vasospasm and causing vascular disruption. Switching fingolimod to other disease-modifying drugs, including dimethyl fumarate, should be considered when non-traumatic hemorrhage is observed in MS patients.